A study of environmental radioactivity measurement of selected Kaolin mining fields in Kwara, Nigeria. Issue 1 (31st December 2022) - Usikalu, Mojisola Rachael; Orosun, Muyiwa Michael; Akinpelu, Akinwumi; Oyewumi, Kayode John
Abstract: This article reports an in-situ measurements of the background gamma radiation dose rates and the activity concentrations of 238 U, 232 Th and 40 K, at kaolin mining-fields in Ilorin-south and Ilorin-west, Kwara, Nigeria. Readings were recorded in 90 randomly selected sample points. For Ilorin-south mining site 50 sample points were recorded, while 40 randomly selected sample points were considered for Ilorin-west mining site. A handheld RS-125 Super-Spec gamma spectrometer was utilized to perform the radioactivity measurements on both mine fields. The results of the activity concentrations showed that the locations are enhanced with 40 K activity concentration compared with 238 U and 232 Th. The mean values of 40 K, 238 U, 232 Th and DR for Ilorin-west were found to be 492.19, 35.63, 44.07 Bqkg −1 and 63.28 nGyh −1, respectively. While the mean values for the measured activity concentrations of 40 K, 238 U, 232 Th and DR for Ilorin-south are 263.55, 52.24, 31.29 Bqkg −1 and 54.71 nGyh −1, respectively. Consequently, the mean values of the estimated radiological hazard parameters of Ilorin-west were higher than the estimated mean values for Ilorin-south. This shows that the Ilorin-west Kaolin mine field poses more significant source of radiation hazard. The results in this current work can be used as a significant baseline radioactivity data of the mining areas in Nigeria for future epidemiology and monitoring purposes.